Thermal barrier coatings failure mechanism during the interfacial oxidation process under the interaction between interface by cohesive zone model and brittle fracture by phase-field. (April 2021) - Zhou, Q.Q.; Yang, L.; Luo, C.; Chen, F.W.; Zhou, Y.C.; Wei, Y.G.
Abstract: Failure of Thermal barrier coatings (TBCs) caused by interface oxidation directly determines the ultimate durability of TBCs. The interfacial delamination and brittle fracture will co-occur during the interface oxidation of the TBCs. To study the interaction between the two failure modes, we develop a thermodynamically-consistent coupling framework combining the phase-field model of the brittle fracture in the bulk material and the cohesive zone model of the pre-existing adhesive interface for TBCs. We divide the critical energy release into two parts to distinguish interface and bulk material failure. According to the variational principle, the phase-field crack evolution equation is obtained. Moreover, the other variables' coupled constitutive and evolving equations are obtained through the dissipation inequality and balance equations. Models and experiments show interface oxidation of APS (air plasma spraying)-TBCs is tending to cracks in the valley of the TC (top coating)/TGO (thermally grown oxide) interface and the peak of the TGO/BC (bond coating) interface. The newly generated TGO will turn the crack at the TGO/BC interface peak into TGO inner crack and eventually lead to equidistant cracks in the TGO peak. Besides, by studying the interaction between cracks at two locations, we find that the TGO/BC interface cracks promote the TC/TGO interface crack initiation and inhibit its propagation. The TC/TGO interface crack very weakly promoted the TGO/BC interface cracks initiation and propagation. The framework present here provides excellent potential for modeling the oxidation failure process in TBCs.